One Hand One Plant: Integrating Climate Change Awareness into Education at PGRI Delta University - Lailatul Musyarofah; Muhammad Fadeli; Rahmatiah; Tri Achmad Budi Susilo (Proceeding International Conference on Digital Education and Social Science, 2024)
Climate change constitutes one of the most significant global challenges, necessitating immediate action and heightened awareness. In response to this, PGRI Delta University launched the "One Hand One Plant" initiative in 2021 as a facet of its dedication to incorporating environmental awareness within the educational framework. This program advocates for the engagement of students, faculty, and staff in the cultivation and care of a tree or plant, thereby fostering a shared sense of responsibility towards sustainability. The initiative aspires to mitigate the campus’s carbon footprint, advance eco-friendly living practices, and inform the university populace about principles of environmental stewardship through real action. This article examines the implementation and the outcomes of the "One Hand One Plant" initiative, illustrating how minor actions can culminate in significant environmental consequences